The Count of Monte Cristo - Dumas, Alexandre (University Press Plc, 2007)
The story opens on a cheerful note with Edmond Dantes sailing into port and being made the captain of the Ship Pharaon, much to the regret of Danglars, the accountant on the ship. The fate of the young man changes in between because Danglars and an aspirant for the hand of Mercedes, Fernand join hands. A conspiracy is hatched. Edmond is arrested...
Keywords: Juvenile Fiction